Strengthening the implementation of the Climate Smart Governance (CSG) Dashboard and the provincial-level consultations to gather insights for enhancing the CSG Dashboard - Alahacoon, Niranga; Amarnath, Giriraj; Sivananthan, Piriyanka (International Water Management Institute, 2024)
Climate change-induced extreme weather events have significantly impacted smallholder farmers in low and middle-income countries, jeopardizing their livelihoods and food security. With more frequent and intense erratic rainfall patterns, droughts, and storms, farmers face heightened risks of crop failure, livestock loss, and property damage. These events also disrupt agricultural cycles and threaten already scarce water resources. The cumulative effects of climate-related disasters perpetuate cycles of poverty and ultimately affect global food security. Transformative climate adaptation solutions coupled with equitable policies are critical to bolster the resilience of these vulnerable communities and safeguard global food security.